Synthesis, characterisation, antioxidant, anti-inflammatory and antibacterial effects of bis- ketone 1,3-Bis (2 acetylphenoxy)-2- propanol: in silico, in vitro and in vivo studies - HARRACHE , Rabiaa; CHAREF , Noureddine Supervisor; KARBAB , Ahlem Co- Supervisor (Setif 1 University - Ferhat ABBAS , Faculty of Technology, 2025)
In this investigation, the bis-ketone 1,3-Bis(2-acetylphenoxy)-2-propanol (Bis-AcPh) was synthesized via the reaction between 1,3-dichloropropanol and 2’-hydroxyacetophenone, and different spectroscopic models, including IR, UV, ¹H-NMR, and ¹³C-NMR, were used to characterize its structure. This bis-ketone was screened for its antioxidant effect by performing DPPH radical scavenging and reducing power methods. In vitro anti-inflammatory activity was estimated using the egg albumin denaturation test, while the topical anti-inflammatory effect was investigated through xylene and croton oil-induced ear edema in mice model. Its antibacterial activity and its cytotoxicity were also tested. On the other hand, some theoretical studies were performed through DFT, molecular docking, ADMET, and MDS predictions. The experimental results demonstrate that the molecule exhibited poor antioxidant activity. Whereas the molecule displayed a potent in vitro and in vivo anti-inflammatory activity. It is noteworthy that the hemolytic degree was less than 2%, this indicates a very low cytotoxicity. Also, the compound showed good antibacterial activity against gram (+) bacteria, especially Staphylococcus aureus. Regarding the computational study results, the Bis-AcPh exhibited the strongest binding affinity to COX-2 among all tested compounds, with favorable interactions within the active site. This observation aligns well with the compound’s confirmed anti-inflammatory activity observed in both in vitro and in vivo assays. ADMET predictions confirmed its good oral absorption, drug-likeness, and synthetic accessibility. Moreover, the toxicity profiling revealed a safe profile with no hepatotoxicity or cytotoxicity. Finally, Molecular dynamics analyses (MDS) revealed that the Bis-AcPh_COX-2 complex exhibited superior overall stability compared to the Aspirin_COX-2 complex
Dans cette étude, le bis-cétone 1,3-Bis (2-acétylphénoxy)-2-propanol a été synthétisé par la réaction de condensation entre le 1,3-dichloropropanol et le 2’hydroxyacetophenone, et l’élucidation structurale du produit a été réalisée à l’aide des méthodes spectroscopiques, notamment IR, UV, RMN (1H, 13C). Ce composé a fait l’objet d’une évaluation de ses propriétés antioxydantes, par les méthodes de piégeage du radical DPPH et par le pouvoir réducteur. L’activité anti-inflammatoire in vitro a été estimée à l’aide du test de dénaturation de l’albumine du blanc d’œuf, tandis que l’effet anti-inflammatoire topique a été étudié à travers le modèle d’œdème de l’oreille induit par le xylène et l’huile de croton chez la souris. Son activité antibactérienne a été évaluée par des bactéries Gram (+) et Gram (-), et sa cytotoxicité a également été examinée. Certaines études théoriques ont été réalisées via DFT, l’amarrage moléculaire, ADMET et les prédictions MDS. Les résultats expérimentaux obtenus indiquent que la molécule présente une activité antioxydante inférieure à celle des antioxydants de référence. En revanche, elle a montré une activité anti-inflammatoire in vitro et in vivo remarquable. Par ailleurs, le degré d’hémolyse observé était inférieur à 2,00 %, ce qui signifie que le composé n’a démontré aucun effet toxique sur les globules rouges. Le composé a présenté une bonne activité antibactérienne vis-à-vis de Staphylococcus aureus. Concernant les résultats de l'étude computationnelle, le Bis-AcPh a montré la plus forte affinité de liaison à COX-2 parmi tous les composés testés. Cette observation concorde avec l'activité anti-inflammatoire confirmée du composé observée lors d'essais in vitro et in vivo. Les prédictions ADMET ont confirmé sa bonne absorption orale, sa similarité médicamenteuse et son accessibilité synthétique. Enfin, les analyses de dynamique moléculaire (MDS) ont révélé que le complexe Bis-AcPh_COX-2 présentait une stabilité globale supérieure à celle du complexe Aspirine_COX-2.
Keywords: bis-ketone; antioxidant; anti-inflammatory; DFT calculation; molecular docking; ADMET prediction; Molecular dynamics analyses (MDS)